Uncertainty and outliers in high‐resolution gridded precipitation products over eastern North America - Picart, Tangui; Di Luca, Alejandro; Laprise, René (International Journal of Climatology, 2024)
Abstract Several observational precipitation products that provide high temporal (≤3 h) and spatial (≤0.25°) resolution gridded estimates are available, although no single product can be assumed worldwide to be closest to the (unknown) “reality.” Here, we propose and apply a methodology to quantify the uncertainty of a set of precipitation products and to identify, at individual grid points, the products that are likely wrong (i.e., outliers). The methodology is applied over eastern North America for the 2015–2019 period for eight high‐resolution gridded precipitation products: CMORPH, ERA5, GSMaP, IMERG, MSWEP, PERSIANN, STAGE IV and TMPA. Four difference metrics are used to quantify discrepancies in different aspects of the precipitation time series, such as the total accumulation, two characteristics of the intensity‐frequency distribution, and the timing of precipitating events. Large regional and seasonal variations in the observational uncertainty are found across the ensemble. The observational uncertainty is higher in Canada than in the United States, reflecting large differences in the density of precipitation gauge measurements. In northern midlatitudes, the uncertainty is highest in winter, demonstrating the difficulties of satellite retrieval algorithms in identifying precipitation in snow‐covered areas. In southern midlatitudes, the uncertainty is highest in summer, probably due to the more discontinuous nature of precipitation. While the best product cannot be identified due to the lack of an absolute reference, our study is able to identify products that are likely wrong and that should be excluded depending on the specific application.

Evaluation of ERA5 precipitation and 10‐m wind speed associated with extratropical cyclones using station data over North America - Chen, Ting‐Chen; Collet, François; Di Luca, Alejandro (International Journal of Climatology, 2024)
Abstract While the ERA5 reanalysis is commonly utilized in climate studies on extratropical cyclones (ETCs), only a few studies have quantified its ability in the representation of ETCs over land. To address this gap, this study evaluates ERA5's skill in representing the ETC‐associated 10‐m wind speed and the precipitation in central and eastern North America during 2005–2019. Hourly data collected from ~3000 stations, amounting to around 420 million reports stored in the Integrated Surface Database, is used as reference. For the spatial‐averaged ETC properties, ERA5 shows a good skill for wind speed with normalized mean bias (NMB) of −0.7% and normalized root‐mean‐square error (NRMSE) of 14.3%, despite a tendency to overestimate low winds and underestimate high winds. The ERA5 skill is worse for precipitation than for wind speed with NMB of −10.4% and NRMSE of 56.5% and a strong tendency to underestimate high values. For both variables, the best and worst performance is found in DJF and JJA, respectively. Negative biases are often identified over regions with stronger precipitation/wind speeds, and a systematic underestimation of wind speed is found over the Rockies with complex topography. Compared to the averaged ETCs, ERA5's performance deteriorates for the top 5% extreme ETCs with a stronger tendency to underestimate both wind speed and precipitation (NMB of −10.2% and −22.6%, respectively). Furthermore, ERA5's skill is worse for local extreme values within ETCs than for spatial averages. Our results highlight some important limitations of the ERA5 reanalysis products for studies looking at the possible impacts of ETCs.

Spatial spin-up of precipitation in limited-area convection-permitting simulations over North America using the CRCM6/GEM5.0 model - Roberge, François; Di Luca, Alejandro; Laprise, René; Lucas-Picher, Philippe; Thériault, Julie (Geoscientific Model Development, 2024)
Abstract. A fundamental issue associated with the dynamical downscaling technique using limited-area models is related to the presence of a “spatial spin-up” belt close to the lateral boundaries where small-scale features are only partially developed. Here, we introduce a method to identify the distance from the border that is affected by the spatial spin-up (i.e., the spatial spin-up distance) of the precipitation field in convection-permitting model (CPM) simulations. Using a domain over eastern North America, this new method is applied to several simulations that differ on the nesting approach (single or double nesting) and the 3-D variables used to drive the CPM simulation. Our findings highlight three key points. Firstly, when using a single nesting approach, the spin-up distance from lateral boundaries can extend up to 300 km (around 120 CPM grid points), varying across seasons, boundaries and driving variables. Secondly, the greatest spin-up distances occur in winter at the western and southern boundaries, likely due to strong atmospheric inflow during these seasons. Thirdly, employing a double nesting approach with a comprehensive set of microphysical variables to drive CPM simulations offers clear advantages. The computational gains from reducing spatial spin-up outweigh the costs associated with the more demanding intermediate simulation of the double nesting. These results have practical implications for optimizing CPM simulation configurations, encompassing domain selection and driving strategies.

Extratropical storms induce carbon outgassing over the Southern Ocean - Carranza, Magdalena M.; Long, Matthew. C.; Di Luca, Alejandro; Fassbender, Andrea J.; Johnson, Kenneth S.; Takeshita, Yui; Mongwe, Precious; Turner, Katherine E. (npj Climate and Atmospheric Science, 2024)
Abstract The strength and variability of the Southern Ocean carbon sink is a significant source of uncertainty in the global carbon budget. One barrier to reconciling observations and models is understanding how synoptic weather patterns modulate air-sea carbon exchange. Here, we identify and track storms using atmospheric sea level pressure fields from reanalysis data to assess the role that storms play in driving air-sea CO 2 exchange. We examine the main drivers of CO 2 fluxes under storm forcing and quantify their contribution to Southern Ocean annual air-sea CO 2 fluxes. Our analysis relies on a forced ocean-ice simulation from the Community Earth System Model, as well as CO 2 fluxes estimated from Biogeochemical Argo floats. We find that extratropical storms in the Southern Hemisphere induce CO 2 outgassing, driven by CO 2 disequilibrium. However, this effect is an order of magnitude larger in observations compared to the model and caused by different reasons. Despite large uncertainties in CO 2 fluxes and storm statistics, observations suggest a pivotal role of storms in driving Southern Ocean air-sea CO 2 outgassing that remains to be well represented in climate models, and needs to be further investigated in observations.

Storms as Forming and Threatening Factors for Coasts - Von Storch, Hans; Feser, Frauke; Blender, Richard; Camargo, Suzana J.; Cavicchia, Leone; Di Luca, Alejandro; Fu, Gang; Gozzo, Luiz Felippe; Koks, Elco; Messmer, Martina; Mori, Nobuhito; Priestley, Matthew D.K.; et al. (Oxford Research Encyclopedia of Climate Science, 2024)
Storms are the most significant meteorological phenomena that affect the formation of coasts and human livelihood along them. Thus, risks related to coastal storms, such as flooding, loss of land, shipping, and other offshore activity, have had a significant influence on coastal societies and their economies. In the early 21st century, anthropogenic climate change will affect the locations and intensities of coastal storminess, impacting society. Storms are studied not only by natural scientists but also by social scientists. The former deal with the climatologies, dynamics, and mechanisms of storms but also with the identification of different types of storms, such as extratropical baroclinic storms, explosive cyclones, tropical storms, polar lows, medicanes, Vb-cyclones, and Australian east coast storms. Their significance is often through their physical impacts, in particular ocean waves and storm surges, which were and are associated with massive losses of lives, sometimes up to several hundred thousand people, and wealth. The perceptions of what storms constitute were different in different cultural contexts and times. In earlier days, higher forces were responsible for such storms, which they used to transfer messages to humans, physically based ideas have been forming since the 16th century. Another significant historical development was societies preparing to reduce their vulnerability to storms and to implement practices of insurance and risk management.